Expanding the Repertoire of Spongian-16-One Derivatives in Australian Nudibranchs of the Genus Goniobranchus and Evaluation of Their Anatomical Distribution - Louise C. Forster; Jack K. Clegg; Karen L. Cheney; Mary J. Garson (Marine Drugs, 2021)
Extracts of the mantle and viscera of the Indo-Pacific nudibranchs Goniobranchus aureopurpureus and Goniobranchus sp. 1 afforded 11 new diterpenoids (1–11), all of which possess a tetracyclic spongian-16-one scaffold with extensive oxidation at C-6, C-7, C-11, C-12, C-13, and/or C-20. The structures and relative configuration were investigated by NMR experiments, while X-ray crystallography provided the absolute configuration of 1, including a 2′S configuration for the 2-methylbutanoate substituent located at C-7. Dissection of animal tissue revealed that the mantle and viscera tissues differed in their metabolite composition with diterpenes 1–11 present in the mantle tissue of the two nudibranch species.